KONFORMITAS REMAJA PADA ASRAMA PANTI ASUHAN PUTRI AISYIYAH DAERAH KAMPAR - Betriyeni Betriyeni; Said Suhil Achmad; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Problem formulation in this research is. Where are the places for conformity in the Aisyiyah orphanage girls' dormitory in the Kampar area? How is the process of adolescent conformity at the boarding school of the daughter of aisyiyah orphanage Kampar? What are the teenagers doing activity or activities of adolescent conformity at the boarding school for orphanage daughter Aisyiyah Kampar area? how is the conformity of adolescents in the daughter of aisyiyah orphanage boarding school Kampar area? This study uses a qualitative approach with descriptive type. Informants in this study are people who are involved and have the information needed in the study, because the informants are people who are more knowledgeable about the issues to be studied. Data collection techniques used were observation, interviews, and documentation, and triangulation of adolescent conformity at the boarding school for girls in the Aisyiyah orphanage Kampar. This study consists of one variable, namely indicators (1) cohesiveness with sub-indicators (a) self-adjustment (b) attention to groups, (2) trust with sub-indicators (a) trust (b) equality of opinion (c) deviation from groups (3) obedience (a) pressure due to rewards, threats or punishment (b) expectations of others ,. The subjects of this study were 5 people consisting of 4 core informants and 1 control informant. Adolescent orphanages in hafsah room carry out joint and compact pickets carry out pickets, Adolescent orphans are able to adjust to the environment around the orphanage, Adolescent orphans adhere to the rules or orders set by the caregiver, Adolescent orphans scramble to queue buckets to take a shower and they meet each other's eyes with little frowning. Key Words: Conformity, Teenagers